Manajemen Kelas dalam Meningkatan Minat Belajar Siswa Di MTs Mamba’ul Barokah NW Borok - Irwan Yon Hadi; Samsul Hadi; Ria Resti Mafika Sari (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Classroom management is all the teacher's activities in the classroom to create and maintain optimal classroom conditions for the teaching and learning process to occur to increase student interest in learning. However, the homeroom teacher at MTs Mamba'ul Barokah NW when the teaching and learning process in the class did not carry out class management properly which caused a lack of interest in student learning. The purpose of the research in this thesis is to find out the classroom management strategy in increasing student interest in learning, the implementation of class management in increasing student learning interest, and the constraints and efforts of class management in increasing student learning interest. The type of research used in this study was qualitative research in descriptive form, the subjects in this study were homeroom teachers and class VII students. Data collection techniques namely observation, interviews, and documentation. The results of the study show that: 1) The classroom management strategy in increasing student interest in learning is by carefully preparing all learning tools in the form of lesson plans using various learning methods and bringing students into the real world so that learning becomes fun and not boring. 2) The implementation of classroom management in increasing student interest in learning is that the teacher uses a variety of teaching methods and continues to develop learning models that are appropriate and ready to help students so that student learning interest increases and maximum learning results are achieved. 3) Obstacles and classroom management efforts in increasing student interest in learning are during the last hour of learning and when the subject matter is considered difficult by students, as well as constraints in terms of limited media provision, this causes student learning interest to decrease.